Is money essential? An experimental approach - Janet Hua Jiang; Peter Norman; Daniela Puzzello; Bruno Sultanum; Randall D. Wright (Bank of Canada, 2023)
Monetary exchange is deemed essential when better incentive-compatible outcomes can be achieved with money than without it. We study essentiality both theoretically and experimentally, using finite-horizon monetary models that are naturally suited to the lab. We also follow the mechanism design approach and study the effects of strategy recommendations, both when they are incentive-compatible and when they are not. Results show that output and welfare are significantly enhanced by fiat currency when monetary equilibrium exists. Also, recommendations help if they are incentive-compatible but not much otherwise. Sometimes money is used when it should not be and we investigate why, using surveys and measures of social preferences.
Keywords: E4; E5; C92; 330; Central bank research; Economic models